2007
DOI: 10.1103/physrevb.75.249901
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Quantitative study of atomic ordering inGa0.5In0.5Pthin films byP

Abstract: In Eq. ͑1͒, the expression for A 2 should be Fig. 4a, curves labeled n = 3 and n = 1 should be exchanged, and curves labeled n = 4 and n = 0 should be exchanged. These corrections have no effect on the conclusions of this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…5 Å of one another). The intense 31 P NMR signal centered at −164 ppm is attributed to P atoms residing in the phosphide core of InP and In 0.50 Ga 0.50 P because this peak has the highest intensity in the spin-echo spectrum, and a similar chemical shift was reported in prior studies of InP and In 1– x Ga x P phases. There is one additional 31 P NMR signal at ca. −119 ppm observed in the spectrum of the InP QDs next to the most intense 31 P NMR signal, which is assigned to subsurface phosphide 31 P atoms .…”
Section: Resultssupporting
confidence: 54%
“…5 Å of one another). The intense 31 P NMR signal centered at −164 ppm is attributed to P atoms residing in the phosphide core of InP and In 0.50 Ga 0.50 P because this peak has the highest intensity in the spin-echo spectrum, and a similar chemical shift was reported in prior studies of InP and In 1– x Ga x P phases. There is one additional 31 P NMR signal at ca. −119 ppm observed in the spectrum of the InP QDs next to the most intense 31 P NMR signal, which is assigned to subsurface phosphide 31 P atoms .…”
Section: Resultssupporting
confidence: 54%
“…The comparison of the experimentally observed populations (Figure a, dots) with the populations resulting for a random distribution (Figure a, dashed lines) shows an overall good agreement, with small but systematic deviations especially for the mixed contact MA–FA (red). This indicates a weak tendency for clustering of MA and FA cations, leading to local fluctuations in composition, which can be quantified by introducing an order parameter S , in analogy to the analysis of XRD data . For a cluster model, an order parameter of S = 0 corresponds to a random distribution, whereas S = 1 characterizes a complete phase separation.…”
Section: Resultsmentioning
confidence: 99%
“…All experiments, including transmission electron microscopy (TEM), [1−3] atomic force microscopy, [4,5] electron diffraction, [2] x-ray diffraction (XRD) [2,6,7] and nuclear magnetic resonance (NMR) [8,9] demonstrated that in A x B 1−x C epilayers A and B atoms on their group III sublattices often show spontaneously partially ordered structure because of surface-induced effects. [10,11] In partially ordered domains of A x B 1−x C epilayers, as shown in Fig.…”
Section: Various Epitaxial Techniques Have Been Utilizedmentioning
confidence: 99%